1998
DOI: 10.1093/hmg/7.11.1761
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of 19 Disease-Associated Missense Mutations in the Regulatory Domain of the Cystic Fibrosis Transmembrane Conductance Regulator

Abstract: In order to gain a better insight into the structure and function of the regulatory domain (RD) of the cystic fibrosis transmembrane conductance regulator (CFTR) protein, 19 RD missense mutations that had been identified in patients were functionally characterized. Nine of these (I601F, L610S, A613T, D614G, I618T, L619S, H620P, G628R and L633P) resulted in aberrant processing. No or a very small number of functional CFTR proteins will therefore appear at the cell membrane in cells expressing these mutants. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 34 publications
5
45
0
Order By: Relevance
“…Similarly, some mutations in the CF gene alter the conduction of the Cl Ϫ channel CFTR, without affecting its targeting (35). Of note, most of these peculiar CF mutations are located within the membrane-spanning domains of CFTR (36,37), and both mutations that were identified here are located within the central hydrophobic domain of NCC: S555L lies at the end of TM10, whereas A588V is within TM12. It has been suggested that the central domain of NCC determines ion translocation and thiazide-binding specificity (38,39), which could provide a basis for the pathogenic role of these missense mutations.…”
Section: Discussionmentioning
confidence: 71%
“…Similarly, some mutations in the CF gene alter the conduction of the Cl Ϫ channel CFTR, without affecting its targeting (35). Of note, most of these peculiar CF mutations are located within the membrane-spanning domains of CFTR (36,37), and both mutations that were identified here are located within the central hydrophobic domain of NCC: S555L lies at the end of TM10, whereas A588V is within TM12. It has been suggested that the central domain of NCC determines ion translocation and thiazide-binding specificity (38,39), which could provide a basis for the pathogenic role of these missense mutations.…”
Section: Discussionmentioning
confidence: 71%
“…The G622D variant, identified in infertile patients, was found at an allelic frequency of 0.18% in a population of African Americans (17 ). Its clinical significance remains unclear, although functional studies have demonstrated a deleterious effect (18 ). One hypothesis is that the G622D phenotype is clinically expressed in intestinal microvilli only during fetal life and is silent thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…Regulation by ATP appeared to be normal; however, the current was much reduced due to a decrease in amplitude of a singlechannel current and also a lower open state probability. More recent studies of Class IV CFTR mutations located within exon 13 that encodes the regulatory domain have demonstrated that these mutations can have different effects on the levels of chloride conductance (Vankeerberghen et al 1998a). Three mutant CFTR proteins, G622D, R792G and E822K, that were transiently expressed in COS cells showed lower chloride channel activities when compared to wild-type CFTR, whereas mutants H620Q and A800G showed increased activities.…”
Section: Class III Mutations Affecting Cl − Channel Regulation/gatingmentioning
confidence: 99%